Wood Waste Valorization and Classification Approaches: A systematic review [version 2; peer review: 2 approved, 1 approved with reservations] - Lucyna Lekawska-Andrinopoulou; AKRIVI KORBA; Kostas Chatziioannou; Angelos Amditis; Georgios Tsimiklis (Open Research Europe)
This systematic literature review delves into various wood waste valorization and classification approaches, aiming to evaluate their efficacy in fostering sustainable wood resource management while enhancing the economic value of wood waste. By synthesizing findings from a diverse array of research studies, the review highlights the multifaceted nature of wood waste valorization, emphasizing the critical role of sorting and separation technologies in ensuring high-quality recovery of materials. It also identifies the wood classification practices in Europe, which are crucial for creating a harmonized valorization framework that aligns technological advancements with regulatory standards. The analysis reveals that integrating these components—technologies, sorting methods, and classification practices can significantly improve the overall efficiency and effectiveness of wood waste management. Furthermore, the review identifies existing gaps in research and practice, providing actionable recommendations for stakeholders aiming to optimize wood valorization waste systems. These recommendations emphasize the necessity for a holistic approach and a clearly defined, comprehensive framework for wood valorization that considers all elements involved in the process. By addressing these areas, the review not only aims to contribute to the body of knowledge in wood waste valorization but also seeks to promote sustainable practices that benefit both the environment and the economy, paving the way for a more circular approach to wood resource utilization.